PENGARUH AKTIVITAS FISIK JALAN KAKI TERHADAP GULA DARAH SEWAKTU PENDERITA DIABETES MELITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS KOTADALAM PESAWARAN TAHUN 2021 - Heru Supriyatno; Diny Vellyana; Diki Stiawan (Healthcare Nursing Journal, 2022)
Background: Lifestyle problems that are risk factors for DM include long time to take corticosteroid drugs, stress smoking, consuming too many carbohydrates, consuming instant food, and obesity. Management of DM patients can be done with daily physical activities and regular physical exercise 3 to 5 days a week for about 30 to 45 minutes. Objective : To determine the effect of physical activity on blood sugar while in patients with Type 2 diabetes mellitus in the Working Area of the Kotadalam Pesawaran Health Center in 2021. Design : quasy experiment with an approach in one group pretest-posttest. Population: Type 2 Diabetes Mellitus sufferers. 166 people using a paired numerical analytical formula by Lemesshow (1997) in Dahlan in 2014 obtained a sample of 16 respondents. Technique The sample uses purposive sampling and primary data types with direct observation data collection techniques by measuring blood sugar levels while using digital glucose (Gluco DR AGM 2100) and the results are recorded on the observation sheet. Analysis of the data in the study using statistical analysis Test dependent sample T test. The results showed that blood sugar variable analysis before walking physical activity averaged 273.44 mg/dl and after walking 170.88 mg/dl. As well as the results of the statistical test, the p-value of 0.000 shows that there is an effect of physical activity on blood sugar in patients with Type 2 diabetes mellitus. balance blood sugar levels are maintained